2021
DOI: 10.1128/mbio.02113-21
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Induced Transmembrane Proteins Inhibit Infection by the Kaposi’s Sarcoma-Associated Herpesvirus and the Related Rhesus Monkey Rhadinovirus in a Cell-Specific Manner

Abstract: IFITM proteins are the first line of defense against infection by many pathogens and may also have therapeutic importance, as they, among other effectors, mediate the antiviral effect of interferons. Neither their function against herpesviruses nor their mechanism of action is well understood.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 85 publications
2
18
0
Order By: Relevance
“…As inhibition of binding to Eph family receptors was obviously not the only mechanism of neutralization, we tested the different anti-gHecto/gL sera in a fusion assay together with the heterologous gB from the related RRV. Use of this heterologous gB is necessary as KSHV gB is not robustly activated for cell–cell fusion by KSHV gH/gL [ 21 , 39 ], but RRV gB is [ 28 ]. RRV gB alone was not fusogenic and barely so in combination with KSHV gH as opposed to strong fusion activity when paired with KSHV gH/gL ( Figure 4 D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As inhibition of binding to Eph family receptors was obviously not the only mechanism of neutralization, we tested the different anti-gHecto/gL sera in a fusion assay together with the heterologous gB from the related RRV. Use of this heterologous gB is necessary as KSHV gB is not robustly activated for cell–cell fusion by KSHV gH/gL [ 21 , 39 ], but RRV gB is [ 28 ]. RRV gB alone was not fusogenic and barely so in combination with KSHV gH as opposed to strong fusion activity when paired with KSHV gH/gL ( Figure 4 D).…”
Section: Resultsmentioning
confidence: 99%
“…The pet11_HIS_STREP_EndoH was ordered from GeneScript and was codon-optimized based on Endo-beta-N-acetylglucosaminidase (aa 32-313) (ref|WP_087792540|) with an N-terminal 6xHis and Strep-tag. The expression construct for KSHV gHecto-FcStrep (original name of the construct in prior publications was gH-FcStrep) as well as pcDNA6-KSHV-gL-Flag, pcDNA6aV5-KSHV-gH, pcDNA6aV5-KSHV-gH I49AE52AF53A [ 27 ], Gal4-TurboGFP-Luc, and the plasmids for the fusion assay were described previously [ 28 , 29 ] (See Table 1 for oligonucleotide sequences).…”
Section: Methodsmentioning
confidence: 99%
“…It is not reported for the first time that IFITMs have different responses to viruses in different cell types. A recent study showed that the overexpression of IFITM2 in SLK cells slightly enhanced Kaposi’s Sarcoma-Associated Herpesvirus (KSHV) infection and significantly enhanced Related Rhesus Monkey Rhadinovirus (RRV) infection ( Hornich et al, 2021 ). Similarly, the overexpression of IFITM1 and IFITM3 consistently enhanced HPV infectivity in several epithelial cell lines and keratinocytes ( Warren et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…This could be ascribed to different cell lines or different tags (Its effect on small proteins should not be ignored). In addition, due to the lack of antibodies, this study used exogenous overexpression of chIFITMs; high levels of exogenously expressed protein could have resulted in abnormal localization and function of the protein to a certain extent ( Hornich et al, 2021 , Bailey et al, 2014 ). Studies have demonstrated that endogenous IFITM can promote SARS-CoV-2 virus infection, whereas exogenously expressed IFITM exerts the opposite effect ( Prelli Bozzo et al, 2021 , Shi et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…We were interested in whether the two envelope genotypes of rhesus macaque foamy viruses differ only in their neutralization sensitivity to antibodies elicited by viruses from their own or the respective other genotype but not in their functionality, or whether the different env variants confer functional differences such as altered cell tropism, which could suggest different receptor tropism or altered sensitivity to cellular restriction factors. Here, in particular, the interferon-induced transmembrane proteins (IFITM) 1-3, which restrict enveloped viruses dependent on their pathway of entry, among other determinants, at the membrane fusion step [ 30 , 31 , 32 , 33 ], are of interest. For FFV, human IFITMs were shown to inhibit FFV at a late stage of infection [ 34 ], hinting at additional antiviral mechanisms.…”
Section: Introductionmentioning
confidence: 99%